Building superior performance: the role of work ethics in a university - Supardin; Nurfatimah; Rahim, Wahida (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2024)
This study uses a quantitative correlation research approach, which aims to examine the relationship between two main variables: Islamic work ethics and employee performance at the State Islamic University of Alauddin Makassar. The study covered a population of 218 individuals, with a sample size 66 employees selected through simple random sampling method. Data collection was conducted through the administration of questionnaires, and the data collected was further analysed using assessment techniques. The analyses included the application of product moment correlation test, F-test, Two-sided hypothesis testing, and Chi-square test. Based on the findings detailed in the previous section of this study, the conclusion of this study is that there is a relationship between Islamic work ethics and the employee performance of UIN Alauddin Makassar. This conclusion is evidenced by the significant value of 0.00, which is greater than 0.05, along with Fcalculate = 17.048 compared to Ftable = 3.98. As a result, H1 is accepted, while H0 is rejected. This confirms the significant influence between Islamic work ethics and employee performance.